Erb-b2 Receptor Tyrosine Kinase 2 (ERBB2) Promotes ATG12-Dependent Autophagy Contributing to Treatment Resistance of Breast Cancer Cells - Chen, Yongqiang (Cancers (Basel), 2021)
SIMPLE SUMMARY: Expression of the tyrosine kinase receptor ERBB2 in cancer cells leads to drug resistance. Autophagy, a “self-eating” process inside the cell, is a mechanism for drug resistance in cancer cells. It has been shown that ERBB2 activation leads to increased autophagy in breast cancer cells, but the underlying mechanisms remains unclear. In this study, we demonstrated that ERBB2 promotes autophagy by increasing the protein levels of the autophagy gene ATG12 (autophagy-related 12), contributing to the resistance of breast cancer cells to chemotherapy drugs or ERBB2-targeted antibody treatments. We further showed that ATG12 expression in breast tumors containing ERBB2 correlated with a worse patient survival outcome. Finally, lapatinib is an inhibitor for both EGFR and ERBB2 tyrosine kinases in the EGFR protein family and promotes autophagy in cells containing only EGFR but inhibits autophagy in cells containing only ERBB2. Taken together, this suggests that ERBB2 promotes autophagy through upregulation of ATG12. ABSTRACT: The epidermal growth factor receptor (EGFR) family member erb-b2 receptor tyrosine kinase 2 (ERBB2) is overexpressed in many types of cancers leading to (radio- and chemotherapy) treatment resistance, whereas the underlying mechanisms are still unclear. Autophagy is known to contribute to cancer treatment resistance. In this study, we demonstrate that ERBB2 increases the expression of different autophagy genes including ATG12 (autophagy-related 12) and promotes ATG12-dependent autophagy. We clarify that lapatinib, a dual inhibitor for EGFR and ERBB2, promoted autophagy in cells expressing only EGFR but inhibited autophagy in cells expressing only ERBB2. Furthermore, breast cancer database analysis of 35 genes in the canonical autophagy pathway shows that the upregulation of ATG12 and MAP1LC3B is associated with a low relapse-free survival probability of patients with ERBB2-positive breast tumors following treatments. Downregulation of ERBB2 or ATG12 increased cell death induced by chemotherapy drugs in ERBB2-positive breast cancer cells, whereas upregulation of ERBB2 or ATG12 decreased the cell death in ERBB2-negative breast cancer cells. Finally, ERBB2 antibody treatment led to reduced expression of ATG12 and autophagy inhibition increasing drug or starvation-induced cell death in ERBB2-positive breast cancer cells. Taken together, this study provides a novel approach for the treatment of ERBB2-positive breast cancer by targeting ATG12-dependent autophagy.